Aspectos da ecologia e comportamento da Myiopsitta monachus no planalto médio do Rio Grande do Sul - Pinto, Fernanda (2020)
Although there has been an increase in studies on biological invasions, there are still few studies that portray consistent perspectives to understand the landscapes and patterns of occurrence of invasive species. In the present study, it was analyzed how Myiopsitta monachus (Boddaert, 1783) interacts in the composition of the landscape, in different landscapes in the city of Passo Fundo, Rio Grande do Sul - Brazil. Patterns of occurrence and habitat composition were determined in three landscapes in which there are occurrences of established populations of the species. The composition of the landscape had clear effects on the occurrence of the species. The occurrence increased with the presence of anthropogenic and agricultural areas in the landscape. The composition of the landscape was strongly related to the patterns of occurrence when the presence of propitious places for nesting and abundance of food were present. The results show that the composition of the rural landscape was the most expressive for the occurrence and permanence of M. monachus, because the conditions were favorable for its establishment. The results also suggest that the greater the anthropic representativeness, the greater the chances of the bird being found in the landscape, as the bird was generalist and opportunistic about the diet, not caring about the human presence, taking advantage of the resources available there.